The efectiveness of narrowband ultraviolet B (NB-UVB) in Vitiligo Management and its Association with Thyroid Stimulating Hormone (TSH) level in Indonesian population - Farida Tabri (DiscoverSys Inc., 2018)
Objective: Vitiligo is an autoimmune disease marked by the presence of hypopigmented macules due to the reduction in the number and function of melanocytes. Besides its adverse cosmetic effect, vitiligo is also associated with other autoimmune diseases such as thyroid disorders. Ultraviolet irradiation, especially narrowband ultraviolet B (NB-UVB), has been widely used in treating vitiligo despite the unclear mechanism. However, such studies in Indonesian population are very limited. This study aims to examine the efficacy of NB-UVB in vitiligo treatment and its effect of thyroid function in Indonesian population.Material and Methods: Twenty-two vitiligo patients aged 4-54 years old were treated three times weekly with NB-UVB. The minimal erythema dose (MED) was determined and an initial dose of 50% MED dose was commenced three times per week. The dose was increased gradually while assessing for the treatment response. The change in depigmentation rate, vitiligo area severity index (VASI), and the level of thyroid stimulating hormone (TSH) were assessed before and after therapy using Wilcoxon test.Results: Depigmentation rate and VASI score were found to decrease after treatment, although the change was not statistically siginificant. Two patients showed an decrease in depigmentation rate of more than 75%. The TSH level significantly decreased after treatment (p>0.05). The most common side effect found was the combination between erythema, soreness, and pruritus.Conclusion: Our study shows that NB-UVB therapy results in improved depigmentation, VASI score and a reduced TSH level in vitiligo patients.